As duas culturas: Antonio Candido e a formação da sociologia e da literatura no Brasil - Segatto, José Antonio [UNESP]; Bariani Júnior, Edison (My University, 2013)
Antonio Candido, author of fundamental papers to understand Brazil’s cultures process formation, in his works about sociology and literature formation, he draws an explanation of these process of cultural genesis by mean of referential and functional systems, that become possible Brazilian society expression though scientific and literary cultures. These processes and explanations look at for functional correlations between elements and system by mean of relationship between authors-works-receptors, nevertheless, it must to investigate the individual contributions of authors and works to formation of shapes and directions of system.

Autor de trabalhos fundamentais para o entendimento do processo de formação das culturas no Brasil, Antonio Candido, em seus trabalhos sobre a formação da sociologia e da literatura no Brasil, esboça uma explicação desses processos de gênese cultural por meio de um sistema referencial e funcional, que torna possível a expressão peculiar da sociedade brasileira por meio da cultura científica e da literária. Tais processos e explicações buscam correlações funcionais entre elementos e sistema por meio da relação entre autores-obras-receptores, cabe então investigar a contribuição individual de autores e obras para a formação de contornos e rumos do sistema.
Keywords: Antonio Candido; Sociology; Literature; Formation; Culture; Antonio Candido; Sociologia; Literatura; Formação; Cultura